EFFECT OF LIQUIDITY ON FINANCIAL PERFORMANCE OF SAVINGS AND CREDIT SOCIETIES IN KENYA - Barus, Jane J.; Muturi, Prof. Willy; Kibati, Dr. Patrick; Koima, Dr Joel (International Journal of Finance, 2017)
Purpose: The purpose of this study was to determine the effect of liquidity on financial performance of savings and credit societies in Kenya. Methodology: The study employed an explanatory research design. The target population was 83 registered deposit taking SACCO's in Kenya that have been in operation for the last five years. The sample size for the study was all 83 SACCOs that have remained in existence since 2011-2015. Census methodology was used in the study. Both primary and secondary sources of data were employed. Multiple linear regression models were used to analyze the data using statistical package for the social sciences (SPSS) and STATA. A pilot study was conducted to measure the research instruments reliability and validity. Descriptive and inferential analysis was conducted to analyze the data. The data was presented using tables and graphs. Results: Based on the findings the study concluded that liquidity influenced the financial performance of savings and credit societies in Kenya. This can be explained by the regression results which showed that the influence was positive and also showed the magnitude by which liquidity influenced the financial performance of savings and credit societies. The regression results showed that liquidity influenced the financial performance of savings and credit societies by 0.019 units. Unique contribution to theory, practice and policy: The study recommended for the deployment of efficient systems to strengthen liquidity risk control fundamentals. SACCO's should also consider seeking professional guidance towards adopting policies on asset and liability management.